Discovering SELF and Purpose in the Arts: The Role of Imagination and Creativity in Transformative Learning and Adult Education’s Responsibility in Facilitating this Learning for Individual and Social Change. - Soni Simpson (Adult Education Research Conference, 2007)
This study introduces a Lotus-Layered Triangulation Model® and an Elements of Being for Transformational Readiness Model® while exploring the role of creativity in transformation. Collage was a powerful arts-based research tool and creative expression found to significantly enhance transformative learning. The research informs program developers about the potential for creative expression in adult education programs for transformation.